The Orientia tsutsugamushi ScaB Autotransporter Protein Is Required for Adhesion and Invasion of Mammalian Cells - Nguyen, Yen Thi Hai; Kim, Chaewon; Kim, Yuri; Jeon, Kyeongseok; Kim, Hong-il; Ha, Na-Young; Cho, Nam-Hyuk (Frontiers in Microbiology, 2021)
Autotransporter proteins are widely present in Gram-negative bacteria. They play a pivotal role in processes related to bacterial pathogenesis, including adhesion, invasion, colonization, biofilm formation, and cellular toxicity. Bioinformatics analysis revealed that Orientia tsutsugamushi, the causative agent of scrub typhus, encodes six different autotransporter genes (scaA-scaF). Although four of these genes (scaA, scaC, scaD, and scaE) are present in diverse strains, scaB and scaF have been detected in only a limited number of strains. Previous studies have demonstrated that ScaA and ScaC are involved in the adherence of host cells. However, the putative function of other O. tsutsugamushi Sca proteins has not been studied yet. In this study, we show that scaB is transcribed and expressed on the surface of O. tsutsugamushi Boryong strain. Using a heterologous Escherichia coli expression system, we demonstrated that ScaB-expressing E. coli can successfully mediate adherence to and invasion into non-phagocytic cells, including epithelial and endothelial cells. In addition, pretreatment with a recombinant ScaB polypeptide inhibits the entry of O. tsutsugamushi into cultured mammalian cells. Finally, we also identified the scaB gene in the Kuroki and TA686 strains and observed high levels of sequence variation in the passenger domains. Here, we propose that the ScaB protein of O. tsutsugamushi can mediate both adhesion to and invasion into host cells in the absence of other O. tsutsugamushi genes and may play important roles in bacterial pathogenesis.